Desenvolvimento de uma plataforma de levitação eletromagnética - Endalecio., Alan Dantas de Medeiros (2018)
This work presents the development of an electromagnetic levitation platform, built at the Laboratory of Applied Superconductivity (LASUP), at COPPE, for educational purposes. Electromagnetic levitation is the main levitation technique currently employed in levitation vehicles, with other applications ranging from toys to industrial equipments. The structure of the platform is similar to the levitation system found in electromagnetic levitation trains, being supported by four magnetic circuits, whose control is done independently. Each magnetic circuit is connected to a complete H-bridge made with IGBT's, responsible for switching the current that is going through the electromagnets, using control signals provided by a Digital Signal Processor (DSP). The control is digitally implemented, using classic controllers for position and current control. The system modeling and controller design are presented as well as simulations to analyze system behavior to variations in reference and presence of certain disturbances. Experimental results are presented with the objective of validating the proposed model and the control techniques used.